2012
DOI: 10.1523/jneurosci.5318-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin (DCX) Mediates Endocytosis of Neurofascin Independently of Microtubule Binding

Abstract: Doublecortin (DCX) is one of two major genetic loci underlying human lissencephaly, a neurodevelopmental disorder with defects in neuronal migration and axon outgrowth. DCX is a microtubule-binding protein, and much work has focused on its microtubule-associated functions. DCX has other reported binding partners, including the cell adhesion molecule neurofascin, but the functional significance of the DCX-neurofascin interaction is not understood. Neurofascin localizes strongly to the axon initial segment in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 57 publications
5
64
0
Order By: Relevance
“…However, knockdown of dynein heavy chain or Lis1 does not affect the cytoplasmic dilation formation, although inhibition of either protein perturbs nuclear forward movement , suggesting that another cellular event is involved in the Cdk5-mediated dilation formation. Although Dcx and Lis1, causative gene products of lissencephaly, share some common functions in the dynein-mediated regulation of centrosome positioning (Tanaka et al, 2004a), Dcx plays other roles in microtubule polymerization and endocytic trafficking (Francis et al, 1999;Gleeson et al, 1999;Friocourt et al, 2005;Moores et al, 2006;Yap et al, 2012), which are shown here to regulate dilation formation. These dynein-independent functions of Dcx may have important roles in dilation formation.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, knockdown of dynein heavy chain or Lis1 does not affect the cytoplasmic dilation formation, although inhibition of either protein perturbs nuclear forward movement , suggesting that another cellular event is involved in the Cdk5-mediated dilation formation. Although Dcx and Lis1, causative gene products of lissencephaly, share some common functions in the dynein-mediated regulation of centrosome positioning (Tanaka et al, 2004a), Dcx plays other roles in microtubule polymerization and endocytic trafficking (Francis et al, 1999;Gleeson et al, 1999;Friocourt et al, 2005;Moores et al, 2006;Yap et al, 2012), which are shown here to regulate dilation formation. These dynein-independent functions of Dcx may have important roles in dilation formation.…”
Section: Discussionmentioning
confidence: 75%
“…One of them, Doublecortin (Dcx), is involved in microtubule polymerization, membrane trafficking and actin organization (Francis et al, 1999;Gleeson et al, 1999;Friocourt et al, 2005;Tsukada et al, 2005;Moores et al, 2006;Yap et al, 2012;Fu et al, 2013). Another, p27 kip1 (Cdkn1b -Mouse Genome Informatics) controls microtubule and actin cytoskeletal organization (Kawauchi et al, 2006;Godin et al, 2012).…”
Section: And P27 Kip1 Control Dilation Formation and Nuclear Elonmentioning
confidence: 99%
“…Dcx-303X behaves as a hypomorph in our assay, suggesting that AP binding might be additionally required for full Dcx function. We previously showed that Dcx promotes the endocytosis of a cell adhesion molecule (24), but further work is needed to explore which endocytic cargo might require Dcx for trafficking to support dendrite elaboration.…”
Section: Lof Alleles For Dendrite Growth Can Map To Mt Binding Ormentioning
confidence: 99%
“…Detergent Extractions-Detergent extractions of live cells were carried out in BRB80 buffer (80 mM Pipes, 1 mM MgCl 2 , 1 mM EGTA, pH 6.8) with 0.3% Triton X-100 at 37°C for 3 min (24,25,26). Cells were washed twice in BRB80 buffer and fixed.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…These include the µ subunits of clathrin adaptor complexes [45] and two kinases, Cdk5 and Jnk [37,46]. Dcx has also been shown to interact with and regulate endocytosis and surface distribution of the phosphorylated neurofascin adhesion molecule [47,48]. Interestingly, this function of Dcx may not involve its microtubule-binding activity.…”
Section: Control Biopsymentioning
confidence: 99%